Perbandingan Ceftriaxone dan Ciprofloxacin dalam Tata Laksana Infeksi Saluran Kemih: Tinjauan Pustaka - Maya Ganda Ratna; Sinta Nurmalasari; Meta Tri Yana; Alvina Christy Maretta; Mariani Mariani; Fiola Yonandes; Alfiya Farah Anindhita (Pusat riset dan Inovasi Nasional, 2026)
Urinary tract infection (UTI) is a common bacterial infection that requires appropriate antibiotic management to prevent complications and antimicrobial resistance. Ceftriaxone and ciprofloxacin are commonly used antibiotics with different clinical indications in UTI treatment. This literature review aims to compare the role of ceftriaxone and ciprofloxacin in the management of urinary tract infections. A narrative literature review was conducted using articles published within the last ten years from PubMed, ScienceDirect, and Google Scholar databases. The review focuses on clinical effectiveness, resistance patterns, and therapeutic considerations. The findings indicate that ceftriaxone is primarily used in moderate to severe or complicated UTIs, particularly in hospitalized patients, whereas ciprofloxacin is more frequently used in uncomplicated UTIs in outpatient settings. However, increasing bacterial resistance and safety concerns limit the empirical use of ciprofloxacin. These findings emphasize the importance of rational antibiotic selection based on clinical conditions and local resistance patterns.